2020
DOI: 10.1542/peds.2019-2314
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Autism Screening and Later Autism Diagnosis

Abstract: OBJECTIVES:To describe the proportion of children screened by the Modified Checklist for Autism in Toddlers (M-CHAT), identify characteristics associated with screen completion, and examine associations between autism spectrum disorder (ASD) screening and later ASD diagnosis. METHODS:We examined data from children attending 18-and 24-month visits between 2013 and 2016 from 20 clinics within a health care system for evidence of screening with the M-CHAT and subsequent coding of ASD diagnosis at age .4.75 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
112
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 27 publications
(15 reference statements)
1
112
0
3
Order By: Relevance
“…In low risk populations the follow-up interview is associated with better prediction, but a similar improvement is not present in high risk groups consisting of children with a sibling diagnosed with ASD (familial risk of ASD) [ 126 ]. Two large studies in the general population reported that M-CHAT-R/F has sensitivities of 33–39% and specificities of 95–98% to detect ASD [ 127 , 128 ]. One of them [ 127 ] indicated that sensitivity at 16–20 months was lower than that at 21–26 months.…”
Section: Early Detection Of Developmental Disordersmentioning
confidence: 99%
“…In low risk populations the follow-up interview is associated with better prediction, but a similar improvement is not present in high risk groups consisting of children with a sibling diagnosed with ASD (familial risk of ASD) [ 126 ]. Two large studies in the general population reported that M-CHAT-R/F has sensitivities of 33–39% and specificities of 95–98% to detect ASD [ 127 , 128 ]. One of them [ 127 ] indicated that sensitivity at 16–20 months was lower than that at 21–26 months.…”
Section: Early Detection Of Developmental Disordersmentioning
confidence: 99%
“…1,2 While the symptoms of ASD can manifest before 2 years of age, they usually become more apparent between 2 and 3 years of age. 1,3 Patients with ASD are all unique in their presentation; however, the disorder is characterized by core symptoms that include impairments in social interaction and communication, as well as the presence of restricted and repetitive behaviors. 1 These symptoms are universal regardless of culture, race, ethnicity, or socioeconomic group.…”
Section: Introductionmentioning
confidence: 99%
“…In the 14 years since the initial AAP screening recommendation, ASD prevalence has increased dramatically (Maenner, 2020), and screening for ASD in primary care has become commonplace. Some estimates suggest that that over 50% of US toddlers are screened for ASD in primary care (Arunyanart et al, 2012), although significant local variability exists (Carbone et al, 2020; Wallis et al, 2020). Increased screening has likely contributed to a decrease in the age of autism diagnosis in the United States: recent data from the Early Autism and Developmental Disabilities Monitoring Network suggest that the percentage of children with ASD diagnosis by the age of 4 years has changed from 58% in 2014 to 71% in 2018 (Shaw et al, 2020).…”
mentioning
confidence: 99%
“…The fact remains that despite widespread autism screening, the majority of children are not being identified with ASD until well past the toddler ages, and this age is even higher for children from low-income and or racial/ethnic minority backgrounds (Durkin et al, 2017; Maenner, 2020). Studies have demonstrated a variety of reasons for diagnostic delays such as (1) not all children attend primary care as toddlers, (2) not all of those who attend are screened for ASD, and (3) not all those who are screened are referred for ASD evaluation (Carbone et al, 2020; Guthrie et al, 2019; Wallis et al, 2020). Furthermore, emerging evidence suggests that ASD screening tools have limited sensitivity—meaning that some children who screen negative on toddler screens go on to receive an ASD diagnosis (Guthrie et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation